A invenção que levou a outros lugares (e das descobertas de um espaço de formação de professores) - Dalmaso, Alice Copetti (2013)
This work has been traced around a series of experimentations lived in the space of an initial teacher's education space, developed in the Training, Knowledge and Professional Development Line (Linha de Formação, Saberes e Desenvolvimento Profissional - LPI) within the Post-Graduation Degree Program at UFSM. These experimentations were thought up and produced out of readings concerning studies in the field of cognition, especially those under the topic of invention, by Virgínia Kastrup. Brought by the author as temporal potency, the invention is not limited to problem solving, it does not submit learning to its results, but rather it enables the continuity of the operation of cognition to non-recognitive experiences and to becoming. Upon meeting with the topic and all which it evoked, questions such as how to feel the invention in an educational space were raised. Thus, through literature, music and images, obscurely, there was a search to experiment another time, other forms of meeting/knowing and of relating during the educational process. Thus the emergency and proliferation of meanings during these meetings led the research/writing process to other meanders, shifting the central position which Kastrup's concept of invention occupied initially in the work to converse with the notion of a meeting as an event and ever ongoing individuation. Describing the narratives of the moments that compose most of the work's part, there has been a writing effort in the sense of showing (and inventing) the veins, lines and compositions, possible and real, of a space where various things converged and diverged, their durations and emergencies. The production of such data, during the construction of reporting the moments lived, became the main labor of this research. Through signs, languages and gestures, the writing process came down to an attempt to expose them, of a possible showing in faces and enunciations, with an intent to disinvest the personal aspect of the event, bringing out a research-writing process that denotes the sensible quality we are made of. To have those means, to make one flow: a movement to vocalize an invention which was not individualized, but above all collective. Authors such as Gilbert Simondon and Gabriel Tarde, then, helped so that such draft of multiple-common - and what makes us unique - would make up most of the work's body. To release the multiplicity of this "me" that is another (oneself/others) which set the tone to the meetings: there are no guarantees, only attempts, and the unfinished research process intended to make seen the uninterrupted movement of lasting and changing. The becoming of this research: make one's own writing as an event, to combine action and affection in its making. Becoming implicated with the desire of giving consistency to collective feeling, without highlights on the truth of what is said, but evidencing the change we own, the singularity we carry (including the researcher's), inventing and making worlds through that feeling. Invention has launched us far and has greatly occupied us. We remain adrift.